Incidence Rates of Pediatric Pseudotumor Cerebri - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Twenty nine cases of pseudotumor cerebri were identified in a retrospective study of records of 205,765 children aged 2-15 years presenting between 1979 and 1994 at the IWK Grace Health Centre, Dalhousie University, Halifax, Canada.